2004
DOI: 10.1111/j.1469-7610.2004.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Major depression and conduct disorder in youth: associations with parental psychopathology and parent–child conflict

Abstract: The implications of these findings for the complex relationship between parental diagnoses, child diagnoses, and parent-child conflict are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
122
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 37 publications
(34 reference statements)
11
122
1
9
Order By: Relevance
“…This may serve as a mechanism for the increased drug and novelty seeking typically engaged in by externalizing individuals, whereby higher levels of stimulation are sought in order to achieve normative responses of the dopaminergic reward system [44]. In contrast, correlates of smoking such a slow socioeconomic status, parental antisocial behaviors, perinatal complications, and poor parenting practices do not show diagnostic specificity and have been associated with both externalizing and internalizing disorders in offspring [45,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…This may serve as a mechanism for the increased drug and novelty seeking typically engaged in by externalizing individuals, whereby higher levels of stimulation are sought in order to achieve normative responses of the dopaminergic reward system [44]. In contrast, correlates of smoking such a slow socioeconomic status, parental antisocial behaviors, perinatal complications, and poor parenting practices do not show diagnostic specificity and have been associated with both externalizing and internalizing disorders in offspring [45,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Parent-child conlict is often found to be a predictor of adolescent externalizing symptomatology [26,27,53]. Eichelsheim et al found that the negative quality of the parent-adolescent relationship, characterized by recurring discord and negative arguments between the parent and the adolescent, was strongly related to the adolescents' levels of aggression, concluding that the negative and coercive interaction paterns in the parent-adolescent relationship seem to sprawl directly into adolescent interpersonal aggression [25].…”
Section: Parent-adolescent Conlictmentioning
confidence: 99%
“…Nevertheless, research has produced ambiguous indings. For example, adolescents' internalizing psychopathology such as major depression disorder (MDD) was associated with high levels of parent-youth conlict [27]. Similarly, Symeou found evidence that both motheradolescent conlict and father-adolescent conlict were predictive of externalizing and internalizing behaviors [43].…”
Section: Parent-adolescent Conlictmentioning
confidence: 99%
“…marital discord, low social class, large family size, paternal criminality, maternal mental disorder, and foster placement, seem to play a predominant causal role in comorbid MDD rather than genetic risk factors [11,12]. Depression in mothers has been identified as a major environmental risk factor for ODD and CD symptoms independent of the presence of ADHD in the children [21,59]. The suggested comorbidity of ADHD and bipolar disorder [6,30] is not supported by a recent family study indicating that bipolar disorder-I in children and adults are the same diathesis, and ADHD is another, unrelated disorder [35].…”
Section: Mdd/anxietymentioning
confidence: 99%